Hunting for Direct CP Violation in B¯s0⟶π+π−K∗0 - Sheng-Tao Li; Gang Lü (Advances in High Energy Physics)
In perturbative QCD approach, based on the first order of isospin symmetry breaking, we study the direct CP violation in the decay of B¯s0⟶ρωK∗0⟶π+π−K∗0. An interesting mechanism is applied to enlarge the CP violating asymmetry involving the charge symmetry breaking between ρ and ω. We find that the CP violation is large by the ρ−ω mixing mechanism when the invariant masses of the π+π− pairs are in the vicinity of the ω resonance. For the decay process of B¯s0⟶ρωK∗0⟶π+π−K∗0, the maximum CP violation can reach −59.12%. Furthermore, taking ρ−ω mixing into account, we calculate the branching ratio for B¯s0⟶ρωK∗0. We also discuss the possibility of observing the predicted CP violation asymmetry at the LHC.